2019
DOI: 10.2979/histmemo.31.2.0078
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Diplomacy in the War Museum: The Case of the German-Russian Museum Berlin-Karlshorst

Abstract: National heritage, and particularly "difficult" heritage, does not exist in isolation from the heritage of other countries. Russia's relationship to Germany is a salient case in point in the Putin era, in which a more cosmopolitan approach to the history of World War II in many European states has been challenged by a reversion to nationalist approaches to this period in Russian memory politics. Taking the example of the German-Russian Museum Berlin-Karlshorst, this article explores the possibilities of and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…Few studies sought to explain the library’s role in cross-cultural relations and cultural cooperation initiated by NGOs and professional organizations such as the United Nations Educational, Scientific and Cultural Organization, the International Federation of Library Associations and Institutions (IFLA), and the ALA. Some studies described museums and art galleries’ role in cross-cultural cooperation involving professional organizations such as the American Alliance of Museums (AAM) and the International Center for the Study of the Preservation and Restoration of Cultural Property (Akagawa, 2014; Beattie et al , 2019; Buchczyk, 2018; Clarke and Woycicka, 2019; Grincheva, 2013; Huang, 2019; McDonald, 2014); one study detailed the role of NGOs, such as the Asia Society, in museums’ cross-cultural relations (Smith et al , 2020) (see Table 8). Instruments…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies sought to explain the library’s role in cross-cultural relations and cultural cooperation initiated by NGOs and professional organizations such as the United Nations Educational, Scientific and Cultural Organization, the International Federation of Library Associations and Institutions (IFLA), and the ALA. Some studies described museums and art galleries’ role in cross-cultural cooperation involving professional organizations such as the American Alliance of Museums (AAM) and the International Center for the Study of the Preservation and Restoration of Cultural Property (Akagawa, 2014; Beattie et al , 2019; Buchczyk, 2018; Clarke and Woycicka, 2019; Grincheva, 2013; Huang, 2019; McDonald, 2014); one study detailed the role of NGOs, such as the Asia Society, in museums’ cross-cultural relations (Smith et al , 2020) (see Table 8). Instruments…”
Section: Resultsmentioning
confidence: 99%
“…Further, museums work with foreign governments abroad as cultural partners and experts to implement grant-based programs such as cultural heritage conservation and museum training (Akagawa, 2014), archaeological site programs (Luke, 2013; Luke and Kersel, 2013), dark heritage and memorial site preservation (Clarke et al , 2017; Clarke and Woycicka, 2019) and partnerships with professional associations such as the AAM and the private sector (Grincheva, 2013, 2015, 2019b), to practice collaborative cultural relations in a liberal independent framework (Walden, 2019) and are not governed by states’ foreign policy agendas and processes (Grincheva, 2019b). We found that museum diplomacy works in a hybrid form of cultural diplomacy strategy where cultural agents, both state and non-state actors, work independently toward a shared goal to establish cultural relations with cultural recipients and partners, whereas libraries are mostly attached to and governed by embassies, consulates and partner cultural organizations, which are mainly mandated by government foreign policy agendas.…”
Section: Discussionmentioning
confidence: 99%
“…In 1943 D. Shostakovich's Leningrad Symphony was performed in London, but in 1944 it was not included in the concert program of the Bolshoi Theatre. In 1943 and 1944, England showed the world its best modern achievements in the field of theatrical and musical art (Clarke and Woycicka, 2019). It is worth noting that the performance at the Royal Albert Hall of Arts and Sciences is not a propaganda show aimed at misleading the world community about London's Allied plans.…”
Section: Discussionmentioning
confidence: 99%
“…Sakaev (2019), D.S.R. Becard and P.M. Filho (2019), D. Clarke and Z. Woycicka (2019), N. Goda and M. Ciefova (2019), P. Korhonen and T. Mori (2020), J. Marinaccio (2020), and many other researchers who have asked questions about aspects of musical art in the political life of countries.…”
Section: Methodsmentioning
confidence: 99%
“…Sometimes the memory wars preceding the military conflicts are played out directly in museum spaces. This was the case, for instance, with the German–Russian Museum Berlin-Karlshorst, where Putin’s increasingly aggressive memory politics hindered the work of the bilaterally composed Academic Advisory Committee and significantly influenced the final shape of the 2013 revised new permanent exhibition (Clarke and Wóycicka, 2019). Thus, what was originally conceived as a place of dialogue and reconciliation becomes yet another battleground.…”
mentioning
confidence: 99%